GAMBARAN KECEMASAN DAN TINDAKAN IBU HAMIL TRIMESTER III DALAM MENGHADAPI PERSALINAN DI MASA PANDEMI COVID-19 DI WILAYAH KERJA PUSKESMAS PAYUNG SEKAKI KOTA PEKANBARU - Humairatun Zakiyah; Sri Wahyuni; Widia Lestari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Untreated anxiety can cause complications during pregnancy that can affect the health of the mother and baby during delivery. Pregnant women who experience anxiety need to take actions that can overcome anxiety. This study aims to explore the anxiety and actions of third trimester pregnant women in dealing with childbirth during the Covid-19 pandemic, especially in the work area of the Payung Sekaki Health Center Pekanbaru City. This study uses a qualitative research method with a phenomenological approach. The sampling technique used is purposive sampling, which is based on criteria that are in accordance with the research objectives. Collecting data using semi-structured interviews, and data analysis using the Colaizzi method. This study got two themes, namely: (1) Anxiety in pregnant women (2) Actions taken by pregnant women in dealing with anxiety before childbirth.Keywords: Anxiety; Third Trimester Pregnant Women; Covid-19 Pandemic; Pregnant Women's Actions.